History of IsIam Umar ibn al-Khattab - Maulvi Abdul Aziz; MAULVI ABDUL AZIZ (Riyadh DARUSSALAM, 2012)
Umar bin al-Khattab, the Second Khalifa of the Muslims Shibli, his biographer, says that in his youth he grazed camels. Before accepting Islam, Umar was one of the most rabid enemies of Muhammad, the Messenger of God.